Милозвучність як естетична ознака мовлення. Особливості евфонії польської та інших слов’янських мов - Gaiseniuk, Olga (Acta Universitatis Lodziensis. Folia Linguistica, 2014)
The essay is dedicated to the esthetical aspect of language. When speaking, people usually pay more attention to the sense of the expression in the lexical level mainly. However vowels are the smallest elements in the system of language, also play rather important role in it. The special use of vowels can influence the perception of the text so that the esthetical function of language is realized. This is the main task of euphony – the phonetic phenomenon of harmonic combination of vowels aimed on the esthetic influence on the recipient. There are several basic aspects of euphony: the variety of vowels, the harmonic combination of vowels according to the simple articulation, the balance between vocals and consonants, the sonority of speech and specific prosody. These phonetic means make the speech melodic and similar to singing. The affect of cacophony appears when pronunciation is difficult or unpleasant to the ear. The Slavic languages among others are also characterized by some means of euphony. The functioning of these means was analyzed on the material of the Lord’s Prayer and International Covenant on Civil and International Law as parallel texts. It was found that in all Slavic languages the balance is kept between vocals and consonants. The processes of assimilation, dissimilation and simplification in the groups of sounds help to achieve the harmony of articulation. Phonetic alternations and morphological changes make speech various. The tendency to euphony appeared in the period of Preslavic language, where the Law of open syllables existed. The Polish language also includes the means of euphony. Their usage was examined in the fragment of radio program. The speakers should formulate their statements according to the aspects of euphony in order to bring the esthetical pleasure for the listeners. Then the speech becomes the real process of creating art.